Effects of age and weather during moult on mountain bluebird Sialia currucoides structural colouration. (12th February 2021) - Ward, Genevieve M.; Mahoney, Sean M.; Joly, Stephen; Reudink, Matthew W.
Abstract : Birds exhibit a vast array of colours and ornaments and while much work has focused on understanding the function and evolution of carotenoid‐based colours (red, orange, yellow), structural colouration (blue, green, purple, iridescent) can also play a key role in sexual signaling. Several studies have examined how factors such age may influence structural colour, however few studies have looked at how structural colour may be influenced by environmental conditions such as variation in weather conditions experienced during moult. In this study, we examined variation in structural colour expression in relation to age as well as rainfall and temperature during post‐breeding moult for a population of mountain bluebirds Sialia currucoides in western Canada over nine breeding seasons. Overall, we found structural colouration was explained by sex, age and weather patterns during moult. At a population level, tail and rump feathers from males were more colourful (higher brightness and chroma, hue values shifted more towards UV) than females, and adults were more colourful than juvenals. Male and female rump feathers generally became less colourful with age. Noise‐receptor colour models revealed colour differences were discernible among sexes, suggesting bluebird colouration is an important sexual signal. Tail and rump plumage variation was associated with weather during moulting periods, though the effects were sex‐ and age‐dependent. Female plumage was generally more colourful following wetter and warmer early summers, while males were more colourful following warmer late summers, and plumage of older birds was more resilient to colour variation due to weather patterns. We suggest that more rainfall may increase insect abundance and thus improve food intake and overall condition of mountain bluebirds. This is one of the first studies to examine how both age and weather conditions concurrently influence the expression of structural colours in birds.